2019
DOI: 10.1038/s41467-019-10429-0
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism to prevent production of reactive oxygen species by Escherichia coli respiratory complex I

Abstract: Respiratory complex I plays a central role in cellular energy metabolism coupling NADH oxidation to proton translocation. In humans its dysfunction is associated with degenerative diseases. Here we report the structure of the electron input part of Aquifex aeolicus complex I at up to 1.8 Å resolution with bound substrates in the reduced and oxidized states. The redox states differ by the flip of a peptide bond close to the NADH binding site. The orientation of this peptide bond is determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 44 publications
(75 reference statements)
2
51
0
Order By: Relevance
“…Detailed structural analysis of the reduced and oxidized NuoEF complex from A. aeolicus revealed that the peptide bond between E95 F and S96 F of NuoF undergoes a reversible flip depending on the oxidation state of the protein (20). In the oxidized state, the carbonyl group of E95 F points to the FMN, while in the reduced state it points to the Fe 2 S 2 cluster (Fig.…”
Section: Implications For Electron Transfer In Other Members Of the Nmentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed structural analysis of the reduced and oxidized NuoEF complex from A. aeolicus revealed that the peptide bond between E95 F and S96 F of NuoF undergoes a reversible flip depending on the oxidation state of the protein (20). In the oxidized state, the carbonyl group of E95 F points to the FMN, while in the reduced state it points to the Fe 2 S 2 cluster (Fig.…”
Section: Implications For Electron Transfer In Other Members Of the Nmentioning
confidence: 99%
“…For the detailed analysis of the structural differences of FdsBG complex to its homologous subcomplex from NADH dehydrogenase, we used the recently published, high-resolution structure from A. aeolicus, NuoEF complex (20). The NuoE subunit is homologous to the Nqo1 and FdsG subunits, and the NuoF subunit is homologous to the Nqo2 and FdsB subunits ( Fig 3A and 3B).…”
Section: Crystal Structure Of Fdsbg Complexoverviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Upstream bi and tetranuclear iron sulfur clusters can also control superoxide production by limiting FMNH - (i.e., t E RED ) lifetime (i.e., t E RED ). An additional (i.e., bypassed in normal electron tunneling from FMN to the Q binding site) binuclear iron-sulfur cluster termed N1a may also modify superoxide production, potentially by sequestering electrons to decrease [FMNH - ] or via a peptide bond gated switch [ 67 , 68 ]. When electron transfer stalls as occurs in the rotenone (a Q binding site inhibitor) inhibited complex, considerable superoxide production can occur ( Figure 2 ).…”
Section: Mechanisms Of Mitochondrial Ros Production: the Knownmentioning
confidence: 99%